Answer:
x=40/33
Step-by-step explanation:
Let's solve your equation step-by-step.
25(4x−3)−2x=45−x
Step 1: Simplify both sides of the equation.
25(4x−3)−2x=45−x
(25)(4x)+(25)(−3)+−2x=45+−x(Distribute)
100x+−75+−2x=45+−x
(100x+−2x)+(−75)=−x+45(Combine Like Terms)
98x+−75=−x+45
98x−75=−x+45
Step 2: Add x to both sides.
98x−75+x=−x+45+x
99x−75=45
Step 3: Add 75 to both sides.
99x−75+75=45+75
99x=120
Step 4: Divide both sides by 99.
99x
99
=
120
99
x=
40
33
Answer:
x=40/33
Answer: 231
Step-by-step explanation: We can use PEMDAS (parentheses, exponents, multiplication, division, addition, subtraction) in order. Multiply 34 and 6: 204.
50 + 204 - 23. Add 50 and 204: 254. Subtract 254 and 23: 231.
Step-by-step explanation:
from,
f (x) = 2x-2+5
BUT x=-2
f (x) = 2 (-2)-2+5
= -4-2+5
= -6+5
= -1
so,
f (x) = -1
The equation would be y = -3/2x + 1/2